(untitled) (Contemporary Mathematics, 2024)
A circular economy uses limited natural resources and is efficient and environmentally productive. It aims to transform from a "take-make-waste" approach to a more restorative and regenerative one. A closed-loop system reduces waste, pollution, and carbon emissions by reusing, sharing, repairing, refurbishing, remanufacturing, and recycling. We developed a new model on reverse logistics economic order quantity with the circular economy. This paper proposes a profit-maximizing economic lot size system in which all products are at variable circularity levels. The product’s degree of circularity directly influences customers’ demand and gross profit per unit, and we study these effects using both linear and nonlinear forms of analysis as consumers become more socially responsible about their consumption practices. This paper aims to maximize profits from the waste of electrical and electronic equipment (WEEE) by reducing carbon emissions. Some examples are discussed to find the profit of a business with variations of parameters. The goal of this study is to help reverse the flow of products to re-manufacturers of electrical equipment, especially computer equipment manufacturers, to acquire the ideal circular index for the products they manufacture to maximize profit and preserve the environment simultaneously.